L'action du directeur d'école : entre interface et coopération au sein de différents réseaux fonctionnels. - Glomeron, Frédéric (Biennale internationale de l'éducation et de la formation et des pratiques professionnelles, 2015)
The school director is a local actor. He has a vital role in the functioning of the school within the territory. Various studies show the importance of his missions in contexts of increasingly complex. Moreover, the world of education is crossed by the use of digital technology, in the daily work of teachers in the classroom and outside of the classroom, in teaching and administrative tasks. This contribution focuses on the work of the school director and seeks to identify its role in collaborative dynamic interface with different types of actors, in various fields of action. The functional networks in which he operates are numerous and the use of digital technology is often at the center of interactions.
Keywords: Activity; Activité; digital; directeur d'école; functional networks; interaction; numérique; réseaux fonctionnels; school director